2005
DOI: 10.1016/j.jasms.2004.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Charge state-dependent fragmentation of oligonucleotide/metal complexes

Abstract: Collision-activated dissociation (CAD) has been employed to assess the gas-phase fragmentation behavior of a series of 1:1 oligodeoxynucleotide (ODN):metal complexes over a range of charge states, using several ten-residue ODNs and a wide array of alkali, alkaline earth, and transition metals. For parent species in low to intermediate charge states, complexation with Ca ϩ2 , Sr ϩ2 , or Ba ϩ2 altered the relative intensity of M-B species, promoting loss of cytosine over loss of guanine. The relative intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…While the interaction of metal complexes with nucleotides is one of the central topics in bioinorganic chemistry, studies about the gas-phase behavior of such interactions are rather scarce [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compared to the numerous papers devoted to the interactions with peptides and proteins. A good knowledge of mechanisms at the molecular level is still lacking in most cases, and to the best of our knowledge, the gas-phase Pb 2+ /nucleotides interactions have not been explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…While the interaction of metal complexes with nucleotides is one of the central topics in bioinorganic chemistry, studies about the gas-phase behavior of such interactions are rather scarce [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compared to the numerous papers devoted to the interactions with peptides and proteins. A good knowledge of mechanisms at the molecular level is still lacking in most cases, and to the best of our knowledge, the gas-phase Pb 2+ /nucleotides interactions have not been explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…The base then leaves the oligonucleotide either protonated or as the neutral base, and the base loss is followed by a backbone cleavage. Studies have also been conducted on the fragmentation of oligonucleotides with a single metal ion attached [27][28][29][30][31][32][33], and Wang et al [34,35] …”
mentioning
confidence: 99%
“…[16][17][18][19][20] Such interactions have important roles in many biochemical processes in cells. [21] Numerous authors have reported that the ESI-MS technique is a major tool in structure elucidation studies of nucleobase derivatives. [22][23][24] In this study, we elaborate on 1, the stability of ligands N-1-(p-toluenesulfonyl)cytosine, (1-TsC) 1, N-1-(methanesulfonyl) cytosine, (1-MsC) 2, their complexes Cu(1-TsC-N3) 2 Cl 2 3 and Cu(1-MsC-N3) 2 Cl 2 4 ( Fig.…”
Section: Introductionmentioning
confidence: 99%